INTEGRASI NILAI SYARIAH DALAM SISTEM KOMPENSASI STRATEGI PENINGKATAN LOYALITAS PEGAWAI PENDIDIKAN ISLAM - Saifullah; Vera Astuti; Eti Hadiati; Junaidah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Compensation in Islamic educational institutions is not only interpreted as a material reward, but must also be based on sharia values as a manifestation of the principles of justice, balance, and moral responsibility. This research aims to examine how the integration of sharia values in the compensation system can act as an effective strategy in increasing employee loyalty in Islamic educational institutions. Using a qualitative approach through literature review and thematic analysis, the study found that a compensation system that adopts sharia principles such as justice (‘adl), maslahat, and amanah - is able to build employees’ emotional and spiritual attachment to the institution. Employee loyalty increases along with transparency, contribution-based rewards, and certainty and blessings in income. The findings emphasise the urgency of a holistic approach to human resource management based on Islamic values to create loyal, professional and dedicated employees.